2020
DOI: 10.3389/fneur.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Acupuncture on the Medical Expenditure and Risk of Depression and Anxiety in Migraine Patients: A Retrospective Cohort Study

Abstract: Background: Migraine, a common neurological disorder, increases the risk of psychiatric disorders. Currently, the efficacy of conventional therapies is considered unsatisfactory. Acupuncture has been gaining popularity in treatment of neuropsychiatric disease. This study aimed to investigate the effect of acupuncture on medical expenditure and the risk of depression and anxiety in migraine patients. Methods: Patients with migraine were either selected for acupuncture treatment or no treatment based on the 1:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…These findings should make clinicians aware of the potential harm that can result from insomnia. Several researchers have reported that acupuncture can effectively reduce PSI, but this information has been presented in the form of protocols that lacked research results (Xiang et al, 2020).Interestingly, past retrospective studies also have found that acupuncture exhibited advantages in treating diseases that developed as sequelae to stroke (Cao et al, 2016;Liao et al, 2020).Although the research topics were not precisely the same, our conclusions were consistent with these studies in that acupuncture was advantageous in treating stroke-related diseases. This was a retrospective clinical study whose primary purpose was to explore the protective factors of PSI, because most previous studies focused on analyzing the risk factors related to stroke.…”
Section: Discussionsupporting
confidence: 82%
“…These findings should make clinicians aware of the potential harm that can result from insomnia. Several researchers have reported that acupuncture can effectively reduce PSI, but this information has been presented in the form of protocols that lacked research results (Xiang et al, 2020).Interestingly, past retrospective studies also have found that acupuncture exhibited advantages in treating diseases that developed as sequelae to stroke (Cao et al, 2016;Liao et al, 2020).Although the research topics were not precisely the same, our conclusions were consistent with these studies in that acupuncture was advantageous in treating stroke-related diseases. This was a retrospective clinical study whose primary purpose was to explore the protective factors of PSI, because most previous studies focused on analyzing the risk factors related to stroke.…”
Section: Discussionsupporting
confidence: 82%
“…17,18 Acupuncture therapy is a widely used treatment to effectively manage migraines, with potential effect. [19][20][21] Numerous studies have shown beneficial effects of acupuncture, including pain relief, 22 improved quality of life (QoL), 23 reduce anxiety, 24 reduce depression, 25 and improved brain function. 26 Evidence-based multicenter randomized controlled trials (RCT) have suggested that real acupuncture (TA) greatly reduces pain reduction compared with sham acupuncture (SA) and improves the QoL and emotional function.…”
Section: Introductionmentioning
confidence: 99%
“…There were minimal adverse effects The data provide support for using EAP as prophylaxis for chronic migraine patients. The authors note the small sample size and discuss how more frequent sessions may increase the treatment’s efficacy Liao et al (2020) [ 46 ] Retrospective study on patients with migraines ( n = 21,209) with 1:1 propensity score matching to control for various demographic information (e.g., sex, age, income). The comparison was between 1948 acupuncture users and 1948 non-acupuncture users There was a statistically significant reduction in cumulative incidence of anxiety, depression, and medical expenditure in the acupuncture users cohort versus the non-acupuncture users cohort The data provide support for using acupuncture in migraine patients with common comorbidities of depression and anxiety Gu et al (2018) [ 44 ] Participants ( n = 45) spread across 3 groups: (1) Migraine without aura (2) Cervicogenic headache (3) Healthy controls The two patient groups received verum accupuncture, while the healthy controls received a sham treatment There was a significant increase in N -acetylaspartate/creatine in the bilateral thalamus after acupuncture treatment in patients with migraines without aura, which was associated with a decrease in headache intensity score Acupuncture significantly increases certain brain metabolites involved in the transmission of pain during migraines, which could explain how acupuncture is able to effectively relieve migraine-associated pain Farahmand et al (2018) [ 48 ] Patients with diagnosis of acute migraine attacks ( n = 60) Some patients received acupuncture, while some patients received a placebo The acupuncture group had significantly lower pain scores at intervals up to 1 h post-treatment; however, there was no significant difference between the two groups at 2, 3, or 4 post-treatment There is no significant difference in pain scores between the acupuncture group and the placebo group following intervention Musil et al (2018) [ 50 ] Patients with a diagnosis of migraines Patients either received acupuncture ( n = 42) or a standard pharmacological treatment ( n = 44) Number of migraine days was reduced more in the acupuncture than the medication group (5.5 vs. 2.0 days) after 12 weeks of intervention.…”
Section: Evidence For Acupuncturementioning
confidence: 99%
“…A Kaplan–Meier analysis with 13-year follow-up data also revealed a statistically significant (log-rank test, p < 0.001) decrease in cumulative incidence of depression and anxiety in the acupuncture cohort. The authors concluded that acupuncture may financially and therapeutically support migraine patients with common comorbidities such as anxiety and depression [ 46 ].…”
Section: Evidence For Acupuncturementioning
confidence: 99%